Possibility of subjective evaluation of different load intensity in amateur boxing training - Kuvacic, G.; Krstulovic, S.; Karnincic, H. (3rd International Scientific Conference: Exercise and quality of life. April 12/13th 2013, 2013)
The aim of this research was to ascertain the possibility of subjective evaluation of different load intensities in amateur boxing training. It was assumed that there was a strong connection between the subjective evaluation of the load intensity and the perceived heart frequency in examinees, with different training load intensities. The sample of examinees in this research consisted of 10 boxers, of average age 21,4±2.2 years, with training experience of 4,9±1.3 years. All the examinees participate in competitions, in following weight classes: -75kg, -81kg, -91kg, +91kg. The sample of variables consisted of 10 measured parameters: the evaluation of subjective load intensity of an examinee (ESLI) in 5 points, and perceived heart frequency (HF)in 5 points of measuring, or, training phases. A modified Borg RPE subjective load intensity scale CR10, ranging from 0 to 10, was used in the evaluation of subjective intensity variables. To ascertain the actual presence of several levels of load intensity, the univariate variance analysis was used for repeated measuring with Fisher LSD test in post-hoc analysis. The insight into the results showed the three levels of load intensity: low, medium and high. The correlation analysis did not show significant relationship between the ESLI and HF variables in the measuring points. The low relation is explained by small number of examinees, relatively low variability of the RPE scale, and the application of only one parameter of objective load evaluation (HF). The research pointed out the importance of subjective evaluation of load intensity, which can be used as a good tool of training process planning and programming.